Shop Floor Culture and Counter School Culture - G.C., Krishna Bahadur; Kshetri, Prabhat Bikram (Journal of Janta Multiple Campus, 2025)
This article investigates the relationship between educational outcomes and anti-school attitudes at different levels of school social organization. Various sociological and philosophical perspectives on shop floor and counter-school culture address a portion of this confusion. The main objective of this study is to verify the effects of shop floor culture and counter-school culture in the field of education. The design of the study involved a descriptive document analysis and the adoption of a systematic literature review. We retrieved the data from books, research papers, and journals. The purpose of this research is to determine the impact of shop floor culture and counter-school culture on students' performance. The theoretical approach draws its foundation from Paul Willis's work. There are various types of shop floor culture that are prevalent in the educational field. These include the belief that private schools provide superior education, the belief that the quality of education is determined by the amount of money invested in schools, the belief that teachers work less and earn more, the belief that knowledge is more important than experience, and the belief that more homework leads to more learning. We conclude that shop floor culture refers to the concepts and behavioural practices of individuals, implying that the cultures of people in different areas will always exhibit slight differences, thereby preventing generalization.